(untitled) (Journal of Agriculture and Environment, 2015)
We investigate whether spatial variations in climatic resource such as rainfall have prompted livelihood diversification, local adaptation and household food availability in Indo-Gangetic Plains using data from a household survey of 2660 farm-families carried out in India, Bangladesh and Nepal. We found that on-farm livelihood sources are higher in high rainfall regime (1300-1800 mm) compared to medium (<1300 mm) and very high rainfall regime (>1800 mm). The off-farm sources are higher in medium rainfall regime. Although a large number of changes are attributed to harvest better yield, yet farmers made numbers of changes in response to climatic variability as well. Although agricultural livelihood and local adaptation are restrained by several climatic and non-climatic factors; the amount of annual rainfall significantly affects livelihood diversification, and the impact of climatic stressors becomes more pronounced when there is interaction with other non-climatic factors. The results imply that livelihood and adaptation strategies should be tailor made along the climatic and non-climatic resources.